2015
DOI: 10.3311/ppso.7993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FDI on Economic Growth: Evidence from V4 Countries

Abstract: There is no way to adequately evaluate the economic development of the V4 countries over recent decades without taking into account the role played in it by foreign direct investment (FDI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…Other reasons from literature are related to spill over issues (Görg and Greenwood, 2003) or financial conditions specific to receiving countries (Hermes and Lensink, 2003). The positive effects of FDI on economic growth in V4 countries were found by Fifeková and Nemcová (2015). However, the authors showed that this positive effect was caused by FDI inflow in the pre-crisis period.…”
Section: Data and Discussion Of Resultsmentioning
confidence: 99%
“…Other reasons from literature are related to spill over issues (Görg and Greenwood, 2003) or financial conditions specific to receiving countries (Hermes and Lensink, 2003). The positive effects of FDI on economic growth in V4 countries were found by Fifeková and Nemcová (2015). However, the authors showed that this positive effect was caused by FDI inflow in the pre-crisis period.…”
Section: Data and Discussion Of Resultsmentioning
confidence: 99%
“…However, only a limited number of studies dealing with similar issues have been conducted in conditions of the Visegrad and Baltic countries. Fifeková and Nemcová (2015) studied among others also the impact of inward FDI on innovation-related performance growth in conditions of the Visegrad countries. They concluded that the presence of foreign investors in these countries not only contributed to technology transfer, but also brought intangible assets such as marketing and management skills, knowledge capital and innovation skills.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Specificky roli FDI ve středoevropském prostoru řešily např. Fifeková, Nemcová (2015). K problematice FDI uvádí, že jsou jedním z klíčových faktorů rozvoje zemí V4.…”
Section: Fdi a Jejich Hodnocení V Kontextu Regionálního Rozvoje V čR unclassified